Mental Toughness and Academic Achievement of Student-Athletes in Junior High Schools - Yahya Eko Nopiyanto; Andes Permadi; Rachman Dani; Ipa Sari Kardi; Ibrahim; Cahyo Wibowo; Ramadhan, Arizky (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to determine the relationship between mental toughness and academic achievement among junior high school student-athletes. This study uses a quantitative approach, using a survey to assess mental toughness and academic achievement. The participants of the study were 109 student-athletes from state junior high schools 18 and 2 Bengkulu City. The findings of the study indicate that student-athletes have mental toughness in the moderate category, and the academic achievement of student-athletes is in a good category. From the results of statistical analysis using SPSS version 22, it is known that there is no relationship between mental toughness and academic achievement among junior high school student-athletes (sig.636 > 0.05). However, the findings show that student-athletes with more mental toughness tend to show higher levels of academic achievement. This study highlights the importance of developing mental toughness not only for sports but also for academic success. This study offers insights for educators, coaches, and policymakers to strive to improve athletic performance and educational outcomes in junior high schools.